Investigation of Mechanical and Physical Behaviours of Polyester Resin Matrix from Recycled Polyethylene Terephthalate with Bamboo Fibre. (10th March 2022) - Kaliappan, Nandagopal; Govindarajan, Venkatesan; Anil Kumar, T CH; Vishnu Kumar, R.; Muthukumaran, S.; Ahamed, Maqusood; Mahadik, Mahadeo A.; Markos, Mebratu
Abstract : In this research article, we investigate the physical and mechanical properties of composites comprised of unsaturated polyester resin (UPR) and recycled polyethylene terephthalate (PET) with 10% to 40% volume of bamboo fibre (BF). Chemical evaluation of BF revealed that BF has a cellulose content of 49.86%, hemicellulose content of 25.17%, and lignin content of 7.14%. As the UPR's different connections, FTIR identified an interconnecting framework between the styrene monomer (ST) and the unsaturated polyester (UP). It was found by TGA-DTG that there were two breakdown phases. UPR's physical and mechanical properties were found to be affected by increasing the amount of fibre in the material, with the water absorption rising from 0.7% to 2.81% and the density (1214.38 to 1168.83 kg/m), flexural strength (51.81 to 28.92 MPa), flexural modulus (2.78 to 2.83 GPa), and tensile strength (9.71 to 3.86 MPa) all decreasing at the same time. On the other hand, the hardness increased from 82.4 Shore D to 67.9 Shore D. Fibre distribution flaws in the UPR were found, affecting the composites' mechanical characteristics. By repurposing two waste products, this study helps create new materials that are better for the surroundings.